PERBEDAAN LITERASI ILMIAH DAN HASIL BELAJAR PADA MATERI SISTEM KOLOID ANTARA PEMBELAJARAN YANG MENGGUNAKAN MODEL INKUIRI TERBIMBING DENGAN METODE EKSPERIMEN RIIL DAN EKSPERIMEN ANIMASI - Nur Chairisa; Arif Sholahuddin; Leny Leny (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2016)
Abstract. The researcher has done a research about teaching learning using guided inquiry model with real expriment and animation expriment in system coloid material at SMA Negeri 1 Martapura batch 2015/2016. The purpose of this research was knowing the difference between scienific literacy and the teaching learning result also students’ feedback among class which used guided inquiry with real experiment and class which used guided inquiry model with animation experiment. This research was included in Quasi Experimental with plan pretest-posttest nonequivalent control group design. The samples of this research were 105 students, which consist of XI MIPA 1, XI MIPA 2, and XI MIPA 3. The samples were choosen using sampling porposive. The researcher was using test technique and non test technique. Analysis data technique used normality test, homogenity test, and anava one way test.The result shows that (1) there was no difference of learning result which significant among learners who used guided inquiry model with real experiment and animation experiment on coloid system material.(2) there was a difference scientific literacy significantly among learners who used guided inquiry model with real experiment and animation experiment on coloid system material and (3) learners gave positive feedback toward teaching learning process which used guided inquiry model with real experiment and animation experiment on coloid system material.Key words: guided inquiry teaching learning model, real experiment method, animation experiment method, learning result, scientific literacy and coloid system.